EDUKASI KESEHATAN MENGENAI PENYAKIT DAN KEPATUHAN MINUM OBAT HIPERTENSI DAN DIABETES PADA LANSIA DI WILAYAH MANUKAN LOR SURABAYA - Rahmad Aji Prasetya; Fitria Abbas Thalib; Bani Bacan Hacantya Yudanagara (Jurnal Abdi Insani, 2023)
The prevalence of hypertension and diabetes among the elderly in East Java reached 63.2% and 21.6%, respectively, making these significant health problems. Controlling these diseases depends on drug adherence, which is also influenced by the patient's level of knowledge. Therefore, a health education program is needed to increase the elderly's knowledge regarding hypertension and diabetes as well as drug adherence. In addition, this program also provides education about the use of curcuma (Curcuma xanthorriza) and cinnamon (Cinnamomum verum) as nutraceutical products. This activity was held for two days at the Manukan Lor Culinary Tourism Center, attended by 25 participants aged 48-81 years; there were 4 men (16%) and 21 women (84%). The material presented on the first day included symptoms, signs, and complications of hypertension and diabetes, lifestyle influence, and drug adherence. Meanwhile, on the second day, there was a presentation and demonstration of making nutraceutical products from ginger and cinnamon. A questionnaire is filled out before and after the presentation to assess the success of education activities. The statistical analysis results showed that this health education activity significantly increased (p=0.002) participants' knowledge regarding hypertension and diabetes mellitus. It was also found that knowledge about medication adherence and lifestyle changes like exercise and low-carbohydrate foods still need improvement.